Challenges in Teaching Science and its Transition to Post-Pandemic Education (American Journal of Multidisciplinary Research and Innovation, 2023)
The COVID-19 pandemic has had a significant impact on the education sector globally, with over one billion students being held out of school as a result of quarantine measures. In response, education systems had to quickly shift to online learning to ensure that students could continue their education. The sudden shift to online learning has resulted in educators having to adapt to the use of technology in education rapidly. The COVID-19 pandemic has highlighted the importance of digital literacy for educators and the need for ongoing training in digital skills. The pandemic has served as an example of emerging, more creative methods of teaching methods, and technology use in education will continue to evolve. Hybrid learning will be critical to delivering realistic educational experiences, and teachers must adapt to become facilitators instead of teachers. The pandemic experience will affect educators’ attitudes towards integrating information and communication technology (ICT) in education, resulting in a rise in the proportion of people who have a favorable opinion of integrating ICT to education. Ongoing training in digital abilities is necessary to gain a viable education. This paper highlights the need for educators to embrace digital literacy and adapt to emerging technologies to provide a quality education in the post-vaccine world.